Microgrid Power Converter Control With Smooth Transient Response During the Change of Connection Mode - Azevedo, Gustavo M. S.; Cavalcanti, Marcelo C.; Neves, Francisco A. S.; Limongi, Leonardo R.; Bradaschia, Fabricio (Eletrônica de Potência, 2014)
Master-slave configuration is a suitable alternative to droop control method to perform the proper power-sharing in microgrids. Microgrids based on master-slave configuration need one master converter (MC) which should be able to work in two operation modes: grid-forming when an outage occurs in the main grid; grid- feeding when the main grid is available. The MC is responsible to control the microgrid voltage and frequency when it is isconnected from the main grid and it also plays an important role during changes of the microgrid connection mode. This paper presents a control scheme that allows the MC operates in both modes (grid- feeding and grid-forming) and proposes a control system management strategy to manage the MC operation under any microgrid connection mode including the transitions between these modes. As a result, the microgrid transient response is smooth during its change of connection mode. Simulations and experimental results are presented to illustrate the feasibility and performance of the proposed control schemes for the MC.